Pengaruh Model Pembelajaran RADEC (Read, Answer Discuss, Explain, and Create) Terhadap Hasil Belajar Peserta Dididik Pada Mata Pelajaran IPAS Kelas V - Septiana; Khairani, Fadhilah; Luthvi Azizah, Alif; Destini, Frida (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2025)
The problem in this study was the low learning outcomes in IPAS for students of grade V at SD Negeri 1 Teluk Pandan. The aim of this study was to determine the effect of the RADEC learning model (Read, Answer, Discuss, Explain, and Create) on the learning outcomes in IPAS. This study used a quantitative approach with an experimental method. The experimental design used was a nonequivalent control group design. The population in this study consisted of 83 students. The sampling technique used was purposive sampling with a total of 55 students. Data collection techniques included tests and observations. Data analysis was performed using the t-test. The results of the study showed that (1) there was an effect of the RADEC learning model on IPAS learning outcomes, as evidenced by the t-test result of t = 10.7 > t-table = 2.021. (2) There was an effect of the problem-based learning model on IPAS learning outcomes, as evidenced by the t-test result of t = 5.487 > t-table = 2.021. (3) There was a difference in the effect between the RADEC learning model and the problem-based learning model on IPAS learning outcomes, as evidenced by the t-test result of t = 2.2 > t-table = 2.021.